1999
DOI: 10.1093/clinchem/45.9.1665
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Characterization of Electrochemical Biosensor Test Strips for Measurement of Glucose in Low-Volume Interstitial Fluid Samples

Abstract: Background: Minimally invasive interstitial fluid (ISF) sampling and glucose measurement technologies were integrated into a hand-held device for diabetic glucose monitoring investigations. Methods: Conventional electrochemical test strip technology (Bayer Glucometer Elite®) was adapted to measure glucose in small (0.5–2.0 μL) samples of ISF. Test strip glucose measurements were performed on a commercial potentiostat and were compared to various reference glucose methodologies (YSI 2300 analyzer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…During each test week the subjects monitored blood glucose at home on one weekday and one weekend day. Blood glucose was measured before breakfast, lunch and dinner, and at bedtime, using Glucometer Elite[13] and test sticks[14]. Tests results were registered together with the subject's notes on possible hypoglycaemic symptoms.…”
Section: Methodsmentioning
confidence: 99%
“…During each test week the subjects monitored blood glucose at home on one weekday and one weekend day. Blood glucose was measured before breakfast, lunch and dinner, and at bedtime, using Glucometer Elite[13] and test sticks[14]. Tests results were registered together with the subject's notes on possible hypoglycaemic symptoms.…”
Section: Methodsmentioning
confidence: 99%
“…9 IF is a relatively passive medium that has onethird of the total protein concentration as compared to plasma with an average albumin=globulin ratio of 1.85. 15 The total body volume of the interstitial space is three times that of plasma; however, IF compartments around the cells are microscopic. 9 IF bathes the cells and feeds them with nutrients, including glucose, by providing a corridor between the capillaries and the cell.…”
mentioning
confidence: 99%
“…The observed increase in data dispersion and bias is in agreement with findings obtained with other cell-free matrices such as plasma (Dr. Ben Feldman, Abbott Diabetes Care, personal communication). Also, the reduced protein content of the ISF as compared with plasma or whole blood may be a source of variability and bias as indicated by Collison et al 27 While the observed bias may easily be corrected by appropriate calibration of the monitor, further investigations are necessary to properly assess the reasons for the wide dispersion of data observed with ISF as the specimen matrix.…”
Section: Discussionmentioning
confidence: 99%